2001
DOI: 10.1002/1522-2683(200101)22:1<77::aid-elps77>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative precision improvements by effective mobility-scale data transformation in capillary electrophoresis analysis

Abstract: By transforming the time-based x-axis of electropherograms in capillary zone electrophoresis (CZE) into the corresponding effective mobility-scale, we propose a simple and robust data representation for a better qualitative and quantitative capillary electrophoresis (CE) analysis. The time scale of the raw electrophoretic data (detection signal versus time) is transformed into an effective electrophoretic mobility scale (mu eff-scale) with account of the electroosmotic flow (EOF) peak or of an internal standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 20 publications
(14 reference statements)
0
39
0
Order By: Relevance
“…In particular, chemical variations on the inner surface can affect the EOF and hence the analyte migration times. SchmittKopplin et al [18] reported that the low reproducibility in migration time was often caused by small changes in the EOF due to uncontrollable alterations of the capillary surface, leading to unpredictable migration time shifts, especially when analyzing actual samples (matrix effects). The adsorption of urine matrices to the inner wall, which may change the surface conditions and vary the EOF, seems to be prevented by the diol moiety.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, chemical variations on the inner surface can affect the EOF and hence the analyte migration times. SchmittKopplin et al [18] reported that the low reproducibility in migration time was often caused by small changes in the EOF due to uncontrollable alterations of the capillary surface, leading to unpredictable migration time shifts, especially when analyzing actual samples (matrix effects). The adsorption of urine matrices to the inner wall, which may change the surface conditions and vary the EOF, seems to be prevented by the diol moiety.…”
Section: Discussionmentioning
confidence: 99%
“…When coupling CE to MS, these major differences need to be fully understood and controlled to optimize the system the best (in terms of reproducibility, sensitivity, selectivity). The dissimilarities are not only due to the fact that the separations are based on relative electrophoretic velocities; this phenomenon per se leads to specific ways to qualitatively (and quantitatively) interpret electropherograms (mobility scale transformation [3,4]). Additionally, two essential processes are responsible for possible variability and need to be kept in mind when switching from chromatography to CE: (i) When injected hydrodynamically, the sample volumes are directly dependent on the viscosity and the type of separation capillary; these parameters thus directly influence the local concentration of sample at the detector (and may cause an under-or overloading).…”
Section: Specificity Of the Separation Technique: Think Ce!mentioning
confidence: 99%
“…Altogether, this entails variability not only in the EOF but also for the t m of the analytes. Therefore, identification of proteins should ideally be based on their µ eff , since this parameter is a unique property of the analyte as long as experimental conditions are well defined [70,71] and will not be affected by EOF fluctuations [71,72]. Although the suitability of this approach has been demonstrated for small molecules, the situation is less straightforward for proteins.…”
Section: Repeatability and Intermediate Precision Of T M And µ Effmentioning
confidence: 99%